Microstructure Degradation of Solid Oxide Fuel Cells Aged in Stack after Long Operation Time up to 20 000h Using 3D Reconstructions by FIB Tomography. (3rd May 2017) - Zekri, Atef; Knipper, Martin; Parisi, Jürgen; Plaggenborg, Thorsten
Abstract : Solid oxide fuel cells (SOFCs) are electrochemical conversion devices, which typically consist of contiguous electrical and ionic conduction solid phases in an interconnected porous structure. The performance of SOFCs as well as their lifetime are strongly dependent on electrode microstructure. In this paper the effects of long exposure time (up to 20 000 h) under realistic operation conditions (T= 850 °C, J= 190-250 mA·cm ‒2 ) in the kinetics of microstructural degradation are investigated for porous Ni/CGO anodes in order to understand the microstructural evolution in SOFC cermet anodes. Data acquired from high resolution and optimized 3D-imaging technique FIB/SEM was used in the quantification of various anode structures aged during different operating time (2 500 h and 20 000 h). The methodologies of SEM-imaging, segmentation and object recognition were improved and this enables a precise quantification of connectivity, tortuosity factor and triple phase boundary length (). Statistically significant 3D microstructural changes were observed in the anode by increasing the operating time, including nickel particle size distribution, changes in connectivity of CGO and a significant decrease of contiguous triple phase boundary densities. The quantitative results was combined with additional qualitative observations, which led to a more thorough description of the complex degradation phenomena in nickel-based cermet anodes.